Female Masculinity in Selected Shake Spearean and Nigerian Plays (2014)
Female masculinity is an expression of male gender traits in females. These masculine traits in female characters have received little attention from scholars of Western and Nigerian literary writings when compared to their focus on the socio cultural constructs of females as weak, soft and inferior. This study, therefore, examined different ways by which some female protagonists in selected Shakespearean and Nigerian plays express related masculine attributes with a view to determining the existence of masculinity features in the plays. The study adopted Derrida‟s Deconstruction and Nussbaum‟s model of Liberal Feminist theories. Eight drama texts were purposively selected based on their thematic affinities for revolutionary attributes in females. These include Shakespeare‟s Merchant of Venice (MV), The Twelfth Night (TN), Macbeth (MAC), and Romeo and Juliet (RJ); Osofisan’s Morountodun and Other Plays (MT), Red is freedom Road (RED), and Sofola’s Wedlock of the Gods (WED) and The Showers (SHO). Data were subjected to literary analysis. Females in Shakespearean and Nigerian drama engage in diverse forms of era-bound masculinity clues to control people and situations. These clues include dress code, voice act, assertiveness and body language. In dress code (transvestism), Viola (TN) and Portia (MV) remain in disguised position, an exclusively male attribute in the Shakespearean period, to win in the law court and to subvert the society‟s ethics of women‟s voicelessness; Titubi (MT) engage in a psychological warfare-fashioned disguise to suppress warlords in their aggressive states. Voice act (mannerisms, soliloquies, prophecies, persuasions) are subtly, but effectively used by all the protagonists. Juliet (RJ) and Viola (TN) use mannerisms and soliloquies with infectious love to exert forces that trap their lovers; Portia (MV), Ibidun (RED), Obinna (SHO) and Ogwoma (WED) use persuasions with doggedness to subvert their men; Lady Macbeth and the witches (MAC) use prophecies to subdue Macbeth. Assertiveness (persistence, coercion, control) cut across the texts. Portia (MV) and Juliet (RJ) use persistence to dismiss the potential suitors dictated by the society; Viola (TN) and Lady Macbeth (MAC) use coercion to assert wills on their men; Titubi (MT), Ibidun (RED), Obinna (SHO) and Ogwoma (WED) use persistence and revolutionary qualities to transform the lives of their people. Body language is displayed by all protagonists, except Ogwoma (WED), Portia (MV), Viola (TN) and Juliet (RJ) who use aesthetic outlooks to entrap their suitors to succumb to their wills. Titubi‟s (MT) use of beauty, courage and determination quell the militant peasants, making the riotous society peaceful. Portia, Viola, Juliet and Lady Macbeth exhibit isolated, individualistic clues while Titubi, Ibidun, Ogwoma and Obinna exhibit masculinities through alliance of assertiveness in the spirit of unionism. Females in Shakespearean plays display all the masculine attributes of dress code, voice act, assertiveness and body language clues, while those in Nigerian drama engage largely in assertive tendency clues. These largely semiotic features establish the era-bound differential exhibition of female masculinity in the dramatic works of Shakespeare, Sofola and Osofisan